2006
DOI: 10.1021/jp055699f
|View full text |Cite
|
Sign up to set email alerts
|

Peracetylated Bovine Carbonic Anhydrase (BCA-Ac18) Is Kinetically More Stable than Native BCA to Sodium Dodecyl Sulfate

Abstract: Bovine carbonic anhydrase (BCA) and its derivative with all lysine groups acetylated (BCA-Ac 18 ) have different stabilities toward denaturation by sodium dodecyl sulfate (SDS). This difference is kinetic: BCA-Ac 18 denatures more slowly than BCA by several orders of magnitude over concentrations of SDS ranging from 2.5 to 10 mM. The rates of renaturation of BCA-Ac 18 are greater than those of BCA, when these proteins are allowed to refold from a denatured state ([SDS] ) 10 mM) to a folded state ([SDS] ) 0.1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…The shape of the peak of ubiquitin remained invariant with decreasing voltage; this observation suggests that the formation of ubiquitin-SDS aggregate at 0.6 mM SDS is rapid relative to the time scale of the CE separation. In the case of BCA at 3 mM SDS, the area of native BCA peak decreased as the residence time of the protein in the capillary increased; we infer that denaturation of BCA at 3 mM SDS occurs on a time scale similar to that of the CE separation (21).…”
Section: Lac (mentioning
confidence: 76%
See 2 more Smart Citations
“…The shape of the peak of ubiquitin remained invariant with decreasing voltage; this observation suggests that the formation of ubiquitin-SDS aggregate at 0.6 mM SDS is rapid relative to the time scale of the CE separation. In the case of BCA at 3 mM SDS, the area of native BCA peak decreased as the residence time of the protein in the capillary increased; we infer that denaturation of BCA at 3 mM SDS occurs on a time scale similar to that of the CE separation (21).…”
Section: Lac (mentioning
confidence: 76%
“…We cannot, therefore, determine a concentration of SDS at which the mobility of these proteins begins to change. *In ␤-Lgb, Asp-64, and Val-118 in isoform A are replaced by glycine and alanine, respectively, in isoform B (21,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A4551). Acetylated variants of BLA were prepared using protocols for the acetylation of other proteins (Gitlin et al 2006c). Briefly, solutions of BLA (1.5 mg/mL or 27 mM BLA, 100 mM HEPBS buffer, pH 9.0, 10.0 mL total volume) were allowed to react with various volumes of acetic anhydride (800 mM acetic anhydride in dioxane) ranging from 0 to 300 mL; the pH of the reaction mixture was monitored with a pH electrode and kept at 9.0 by the addition of NaOH.…”
Section: Chemical Modification Of A-amylasementioning
confidence: 99%
“…We used acetic anhydride to acetylate the lysine residues of CA (this procedure is quantitative; see Supporting Information); we refer to crystals of the peracetylated variant as [CA-(NHCOCH 3 ) 18 ] -19 . Capillary electrophoresis confirmed that all 18 residues were acetylated (Figure S1) 16 ; X-ray crystallography allowed us to determine its structure, and, thus, permitted a comparison with the structure of wild-type CA, 6 which we, hereafter, refer to as [CA-(NH 3 + ) 18 ] -3. 4 .…”
Section: Introductionmentioning
confidence: 94%